Answer:
![(x)/(2) = ((y - 5))/(5)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/22uthqqsqtr2wlp0yd62zr253g6iecb704.png)
Explanation:
We are given the equation
.......... (1) and we have to find the equivalent expression for above expression from options.
Now, the expression can be rearranged as
![((x + 2))/(2) = (y)/(5)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/nt3iq8jnf3ec42mcjtzow37pqv4seyryrg.png)
⇒
![((x)/(2) + 1) = (y)/(5)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/lid057y75ey6esp7jp3ir3wjzr5mrjdon9.png)
⇒
![(x)/(2) = (y)/(5) - 1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/dlrvpbmzeoy4r0kb7llasltdmj1d2z68v3.png)
⇒
![(x)/(2) = ((y - 5))/(5)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/22uthqqsqtr2wlp0yd62zr253g6iecb704.png)
Therefore, this
will be true for the expression (1). (Answer)